Challenges of Citizen Elections Observation in Nigeria: A Historical Perspective - Eleagu, Greene Ifeanyichukwu; Eleagu, Gloria Obiageri (European Scientific Journal, ESJ, 2019)
The near six decades of Nigeria as an independent nation has been fraught with instability arising essentially from attempts at democracy through periodic elections. These elections have been largely chacterized by hooliganism, ballot-snatching, theft of election materials, kidnapping of political opponents, assassination of political rivals, arson, assault and physical destruction of election materials and even intimidation and outright molestation or killing of election officials. This paper therefore went down the memory lane to establish and, using the Marxist theory of state attempt to explain, the pattern of elections that have characterized democracy in Nigeria and locate the place of citizen observers in Nigerian elections.